2011
DOI: 10.1155/2011/465845
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppressor Gene-Based Nanotherapy: From Test Tube to the Clinic

Abstract: Cancer is a major health problem in the world. Advances made in cancer therapy have improved the survival of patients in certain types of cancer. However, the overall five-year survival has not significantly improved in the majority of cancer types. Major challenges encountered in having effective cancer therapy are development of drug resistance by the tumor cells, nonspecific cytotoxicity, and inability to affect metastatic tumors by the chemodrugs. Overcoming these challenges requires development and testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…The remaining 5 mice per treatment group were used for counting extrapulmonary lung nodules as previously described [25, 33, 35]. Briefly, 10 ml of Bouin’s fluid was intratracheally injected into the lungs of sacrificed mice.…”
Section: Methodsmentioning
confidence: 99%
“…The remaining 5 mice per treatment group were used for counting extrapulmonary lung nodules as previously described [25, 33, 35]. Briefly, 10 ml of Bouin’s fluid was intratracheally injected into the lungs of sacrificed mice.…”
Section: Methodsmentioning
confidence: 99%
“…It has been proved that TSGs contribute to drug resistance in several types of solid tumors. For example, TSGs including E1A, p53, Fhit, IL-24, Fus1 and BiKDD are associated with drug resistance in ovarian, lung and pancreatic cancer, and these genes are potential genes for gene therapy (10). In this study, on the basis of published reports, 15 TSGs which contributed to drug resistance in ovarian cancer were reviewed to provide an overview of the relationship of TSGs with ovarian cancer drug resistance; meanwhile, protein interactions and bio-association analysis were performed to demonstrate the associations of these TSGs and to mine the potential drug resistance-related genes which are closely related to the 15 TSGs.…”
Section: Tumor Suppressor Genes Associated With Drug Resistance In Ovmentioning
confidence: 99%
“…Previous studies have confirmed that the transfection of tumor suppressor genes can significantly reduce the growth and metastatic ability of breast cancer cells (5). Breast cancer suppressor candidate-1 (BCSC-1; also termed von Willebrand factor A domain containing 5A and LOH11CR2A) is a newly identified tumor suppressor gene localized at chromosome 11q23-q24.…”
Section: Introductionmentioning
confidence: 95%